PENGARUH SEDIAAN GEL EKSTRAK KULIT KAYU MATOA (Pometia pinnata) TERHADAP LUKA MEMAR PADA PAHA TIKUS (Rattus norvegicus) - Khoiruzaman, Mahmud Sulthon; Muslihin, A. M.; Astuti, Ratih Arum (Jurnal Farmasindo: Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Matoa is a plant endemic to Papua, has antioxidant properties in its bark, which has the potential to treat bruises, a health problem that requires convenient product innovation. Thus, this study aims to test the effectiveness of matoa bark extract gel (Pometia pinnata) on bruises in white mice. This study is a quantitative experimental study. The gel was tested at extract concentrations of 1.5%, 3%, and 4.5%. Wound measurements were carried out using calipers, and observation notes were analyzed using two types of statistical tests: two types of paired and independent sample T-tests. The results showed that matoa bark extract contains saponins and flavonoids as antioxidants, anti-inflammatories, terpenoids that function as collagen stimulants. All treatment groups showed a significant healing effect. Gel concentrations of 3% and 4.5% gave significant results, although the 3% gel did not provide an effect equivalent to the positive control. The 1.5% gel had the same effect as the negative control. In conclusion, matoa bark extract gel with concentrations of 3% and 4.5% had a significant effect on healing bruises, although the 3% concentration of matoa bark extract gel did not provide an effect equivalent to the positive control.